2019
DOI: 10.1177/1534734619856143
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aCeratothoa oestroidesOlive Oil Extract in Patients With Chronic Ulcers: A Pilot Study

Abstract: Chronic wounds unresponsive to existing treatments constitute a serious disease burden. Factors that contribute to the pathogenesis of chronic ulcers include oxidative stress, comorbid microbial infections, and the type of immune system response. Preclinically, and in a case study, a formulation containing a Ceratothoa oestroides olive oil extract promoted wound healing. Patients with chronic venous and pressure ulcers, clinically assessed as being unresponsive to healing agents, were treated for 3 months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
10
0
3
Order By: Relevance
“…In a pilot study, Vitsos et al examined the effect of Ceratothoa oestroides olive oil extract in people with chronic ulcers. Treatment was evaluated using the Bates-Jensen scale, and the results showed that the overall wound score decreased by 36% ( P < 0.001) [ 9 ].…”
Section: Topical Applications Of Olivementioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study, Vitsos et al examined the effect of Ceratothoa oestroides olive oil extract in people with chronic ulcers. Treatment was evaluated using the Bates-Jensen scale, and the results showed that the overall wound score decreased by 36% ( P < 0.001) [ 9 ].…”
Section: Topical Applications Of Olivementioning
confidence: 99%
“…e evergreen olive tree (Olea europaea) is a natural source of antioxidants and other bioactive compounds that come from different parts of the olive [3]. e effectiveness of olives on wound healing has been investigated in several studies [4][5][6][7][8][9][10][11][12]. In general, olives have antioxidant, antibacterial, anti-inflammatory [13], and antiviral properties and, therefore, can facilitate the repair of epithelial tissue, which is effective in the wound healing process [14].…”
Section: Introductionmentioning
confidence: 99%
“…Is the topical dose 2%w/w of AcOH optimal or could it be further improved by applying a different dose? The choice of 2% was not arbitrary, as acetic acid is usually used topically in doses ranging from 0.5 to 5%w/w and 2% is frequently applied topically for pseudomonas aeruginosa infections [40,41] . Another weakness is the non measurability of ILs characteristic of psoriasis like, IL17, IL17A, IL23 and TNF-α in the case of the hairless model ApoE/SKH-hr2.…”
Section: Based On Our Data (Figuresmentioning
confidence: 99%
“…Recent studies showed increased wound contraction and wound tensile strength when treated with extracts of Olea europaea [23]. In modern day studies, olive oil exhibited substantial wound healing efficacy in chronic wounds [24]. However, the antimicrobial capacity is limited [25].…”
Section: Plant-based Productsmentioning
confidence: 99%